American mosaic : immigrants in American history - Macmillan Publishing Company (Macmillan Pub. Co., 1975)
Places the history of immigration to the United States in the broader context of American history. Encourages an understanding of the different qualities of the diverse ethnic groups which came to America.
Library has 414 slides in 4 carousels.
Also issued with phonodiscs.
With teacher's guide.
Written by Jerome Ozer.
Keywords: Minorities -- United States; United States -- Emigration and immigration -- History